Inclusive Education for Autistic Learners in Trinidad and Tobago: Policy, Evidence, and Implementation Capacity - Gabriel Julien (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
Inclusive education requires meaningful participation and support, not just placement. Evidence on how autistic learners participate and receive support in mainstream classrooms in Trinidad and Tobago remains limited and mostly disability-wide rather than autism-specific. This review examined learner participation, classroom practice, teacher preparedness, assessment, and policy implementation while distinguishing direct autism evidence from the national and regional contextual evidence. A structured narrative review screened a reconstructed corpus of 47 unique candidates through separate scholarly and policy document streams; 31 analytical sources were included, comprising 15 scholarly sources and 16 policy, legal, or technical documents. International evidence supports a participation-oriented interpretation and identifies potentially useful structured, individualized, communication-oriented, and participation-focused practices, although implementation appears to be contingent on training, resources, role clarity, collaboration, and organizational support. National sources document a substantial policy foundation alongside incomplete accommodations and continuing capacity, coordination, data, and accountability constraints. No included source evaluated a comprehensive local autism-inclusive classroom model. The findings suggest prioritizing usable school guidance, practice-based teacher development, coordinated specialist support, and participation-linked monitoring while evaluating internationally derived practices locally.